The Influence of Budget Participation, Motivation, and Competence on the Managerial Performance of Datu Kandang Haji Hospital - Diah Afrianti; Kadir Kadir; Sarwani Sarwani (Green Publisher Indonesia, 2025)
Diah Afrianti (2024), The Effect of Budget Participation, Motivation, and Competence on Managerial Performance at Datu Kandang Hospital. Supervisor I: Dr. Kadir, Drs, M.Si, Ak, CA. Supervisor II: Dr. Sarwani, Drs, Ec, M.Si, Ak, CA, CPA. The purpose of this study is to examine several factors that affect managerial performance. Some of the factors tested and analyzed are budget participation, motivation, and competence at Datu Kandang Haji Hospital. The sample used in this study were managers at Datu Kandang Haji Hospital. The sample selection method uses the saturated sampling method (census), which is a sampling technique if all members of the population are used as samples. The number of managers sampled in this study were 33 managers. The data analysis technique used is multiple linear regression analysis using the SPSS version 25 program. The results showed that budget participation has a positive effect on managerial performance. Motivation and competence have no effect on managerial performance at Datu Kandang Haji Hospital.